Analysis of Consumer Satisfaction Through Purchase Decisions with Credibility and E-Wom - Shayyid Maulana, Hilman; Abdul Aziz, Muh; Amal, M Khairul (Lafadz Jaya Publisher, 2024)
Research on consumer satisfaction through purchasing decisions with credibility and electronic word-of-mouth (e-WOM) on Shopee users in Sukabumi Regency has been widely conducted, but few have analyzed the relationship in depth between these variables. The purpose of this study is to analyze and explain the influence of credibility and e-WOM on purchasing decisions that have an impact on consumer satisfaction. The research method used is quantitative. The population in this study were active Shopee users in Sukabumi Regency, and the sample was taken using a non-probability method of 130 respondents. Data were collected through an online questionnaire (Google Form). The analysis technique used was Structural Equation Modeling (SEM). The results showed that there was a significant influence of credibility and e-WOM on purchasing decisions and consumer satisfaction, with a coefficient of determination of 70.3% for purchasing decisions and 41.1% for consumer satisfaction. The contribution of this study is to provide recommendations to e-commerce business actors to strengthen credibility and utilize e-WOM in an effort to increase consumer satisfaction, as well as assist researchers in developing further studies related to consumer behavior on e-commerce platforms.